METODE PELAKSANAAN JEMBATAN UNDERPASS KERETA API BEBEKAN DAN ANALISA KAPASITAS DUKUNG TIANG DENGAN METODE SPT PROYEK PEMBANGUNAN JALAN TOL SURABAYA-MOJOKERTO SEKSI IB - , LILIK FAJAR P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bridges as a means of transport has an important role for the smooth movement of traffic. The bridge is a construction that is pointless to continue the path that was interrupted due to barriers such as rivers, swamps, other roads, railroads. The reason the construction of the Surabaya-Mojokerto toll road because of frequent congestion due to the number of vehicles exceeding the capacity of the road, it would require the construction of toll roads in order to facilitate the flow of traffic and the public economy Bebekan railway underpass bridge consists of a structure above the pier head, girders, floor plate while the bottom structure that column, footing, which bore pile foundation pile bearing capacity is calculated by the method of SPT. The results of the calculation of bearing capacity of foundation based on the SPT data have different results but used the axial bearing capacity axial bearing capacity of the smallest.